Antimicrobial compounds from endophytic Streptomyces sp. BCC72023 isolated from rice (Oryza sativa L.) - Supong, Khomsan; Thawai, Chitti; Choowong, Wilunda; Kittiwongwattana, Chokchai; Thanaboripat, Dusanee; Laosinwattana, Chamroon; Koohakan, Prommart; Parinthawong, Nonglak; Pittayakhajonwut, Pattama (My University, 2016)
An endophytic actinomycete strain BCC72023 was isolated from rice (Oryza sativa L.) and identified as the genus Streptomyces, based on phenotypic, chemotaxonomic and 16S rRNA gene sequence analyses. The strain showed 99.80% similarity compared with Streptomyces samsunensis M1463T. Chemical investigation led to the isolation of three macrolides, efomycins M (1), G (2) and oxohygrolidin (3), along with two polyethers, abierixin (4) and 29-O-methylabierixin (5). To our knowledge, this is the first report of efomycin M being isolated from a natural source. The compounds were identified using spectroscopic techniques and comparison with previously published data. All compounds exhibited antimalarial activity against the Plasmodium falciparum, K-1 strain, a multidrug-resistant strain, with IC50 values in a range of 1.40-5.23 μg/ml. In addition, these compounds were evaluated for biological activity against Mycobacterium tuberculosis, Bacillus cereus, Colletotrichum gloeosporioides and Colletotrichum capsici, as well as cytotoxicity against both cancerous (MCF-7, KB, NCI-H187) and non-cancerous (Vero) cells.
Keywords: Antimicrobial; Efomycins; Endophytic actinomycete; Macrolides; Secondary metabolites; Streptomyces